The Influence of High-Intensity Interval Training (HIIT) on VO2Max Improvement in Basketball Extracurricular Participants at SMAN 5 Malang for the 2024/2025 Academic Year - Huda Trisena Laila Agusta (Journal of Strength and Conditioning, 2024)
This study aims to analyze the effect of the High-Intensity Interval Training (HIIT) program on improving VO₂Max in students participating in the basketball extracurricular activity at SMA Negeri 5 Malang. The training program was designed to enhance cardiorespiratory endurance, which is a crucial component in athletic performance. The study was conducted over six weeks, with a training frequency of three times a week on Mondays, Wednesdays, and Fridays, starting from October 7 to November 18, 2024. The research subjects consisted of 25 students in the experimental group. Data were collected through the Multi-Stage Fitness Test (MSFT) conducted before (pretest) and after (posttest) the training program.The results showed a significant improvement in the students' VO₂Maxafter participating in the HIIT program. The average VO₂Max value increased from 42 in the pretest to 42.7 in the posttest, with an average increase of 0.7 or equivalent to 1.66%. The median value increased from 41 to 42, while the mode value showed a significant change from 37.1 in the pretest to 51.6 in the posttest. Additionally, the standard deviation decreased from 6.43 to 6.39, indicating a more homogeneous data distribution.The paired sample t-test showed a t-value of 16.4, which is much greater than the t-table value of 1.71, with a significance value of <0.001. This proves a significant difference between the pretest and posttest results. Thus, it can be concluded that the HIIT program has a significant impact on increasing VO₂Max.This study demonstrates that HIIT is an effective and efficient training method that can be widely applied to improve cardiorespiratory endurance, particularly in young athletes. These findings provide scientific contributions to the field of sports science and can serve as a reference for sports coaches in designing evidence-based training programs. The HIIT program is not only relevant for basketball but also for other sports that require high cardiorespiratory endurance.